2023
DOI: 10.3390/su15021096
|View full text |Cite
|
Sign up to set email alerts
|

How Do E-Brand Experience and In-Store Experience Influence the Brand Loyalty of Novel Coffee Brands in China? Exploring the Roles of Customer Satisfaction and Self–Brand Congruity

Abstract: China’s coffee sector is experiencing a transformation related to sustainability. While the media have reported various novel coffee brands in China, scholars have mostly focused on established non-Chinese coffee brands. These studies still cite the relevance of the growing middle class, which adopts coffee as part of an ‘exquisite Western lifestyle’ and form the antecedents of brand loyalty from an established coffee brand perspective. These antecedents may not directly apply to novel coffee brands that face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…Memberikan e-brand experience yang maksimal dapat mendorong konsumen untuk meningkatkan pengalaman berbelanja online yang baik memengaruhi perilaku belanja online konsumen. In-store experience dalam coffee shop ditentukan dari kualitas layanan dan design bagunan yang di rancang untuk membuat konsumen merasa nyaman dengan suasana yang diberikan (Pu et al, 2023). Kerangka konseptual dalam penelitian ini dapat digambarkan sebagai berikut:…”
Section: Rerangka Konseptualunclassified
See 3 more Smart Citations
“…Memberikan e-brand experience yang maksimal dapat mendorong konsumen untuk meningkatkan pengalaman berbelanja online yang baik memengaruhi perilaku belanja online konsumen. In-store experience dalam coffee shop ditentukan dari kualitas layanan dan design bagunan yang di rancang untuk membuat konsumen merasa nyaman dengan suasana yang diberikan (Pu et al, 2023). Kerangka konseptual dalam penelitian ini dapat digambarkan sebagai berikut:…”
Section: Rerangka Konseptualunclassified
“…menyatakan bahwa menciptakan E-brand experience yang unik mampu membuat konsumen mengunjungi website secara berulang-ulang. Pu et al,(2023) menyatakan bahwa E-brand Experiece memiliki pengaruh positif terhadap kepuasan konsumen. Maka hipotesis dalam penelitian ini dapat dirumuskan sebagai berikut:…”
Section: Gambar 1 Rerangka Konseptual Hipotesisunclassified
See 2 more Smart Citations
“…In the path analysis, SBC positively influenced loyalty and acted as a perfect mediator between CEB and loyalty. Pu et al (2023) conducted a study on how interactions with a brand, both online and in-store, affect customer satisfaction and loyalty, considering self-identification with the brand. Based on an online survey of 332 customers of new Chinese coffee brands, the study revealed that both online and in-store experiences equally impact satisfaction, influenced by self-brandidentification.…”
Section: Introductionmentioning
confidence: 99%